Causal associations between dietary habits and liver cancer risk: a two-sample Mendelian randomization study - Wen-Hao Hu; Jia-An Sun; Chang Liu (Discover Oncology)
Abstract Background Liver cancer is among the most prevalent cancers worldwide and is the second leading cause of cancer-related death. Epidemiological evidence suggests a potential correlation between dietary habits and the incidence of liver cancer. However, establishing a definitive causal relationship remains uncertain. Mendelian randomization (MR) is frequently employed to investigate the causal link between exposure and results. Aim This research focuses primarily on exploring and confirming whether there is a causal connection between dietary choices and the risk of liver cancer. Methods Exposure data, encompassing various dietary habits such as the consumption of dried and fresh fruits, both cooked and raw vegetables, types of fish (oily and nonoily), and beverages such as tea and coffee, as well as different meats (poultry, beef, pork, and processed), were obtained from the UK Biobank. Conversely, outcome data were derived from the FinnGen study. Inverse variance weighting (IVW) was predominantly employed to assess the causal relationship. To ensure the validity of our findings, rigorous tests for heterogeneity and horizontal pleiotropy were conducted. Results Our MR study findings revealed a significant association, indicating that genetically influenced oily fish intake is linked to a lower risk of liver cancer (OR = 0.160, 95% CI 0.026–0.968; P = 0.046). However, no substantial causal connections between liver cancer and the intake of other dietary habits were observed. Importantly, our two-sample MR investigations indicated no considerable pleiotropy effects in the instrumental variables (IVs). Conclusion In summary, our findings suggest a potential protective effect of oily fish intake against liver cancer, emphasizing the need for further studies to validate these results.